unspoken poems for a passed lover - Lavin, Madeleine (UnderCurrents: Journal of Critical Environmental Studies, 2022)
This selection of poetry is grounded in personal memory, written for a former lover but never shared with the intended before they died. These love poems are informed by a posthuman perspective that looks at relationships between human beings and the more-than-human world drawing on assemblage theory, environmental temporalities, and a metaphorical new materialism.